Merespon Retorika Populisme: Analisis Naratif Pemberontakan Bilangan 16 dalam Perspektif Manajemen Konflik - Pieter Anggiat Napitupulu (Sekolah Tinggi Alkitab Penyebaran Injil (STAPIN) Majalengka, 2026)
This article analyzes Moses' leadership response to populist rhetoric in Numbers 16 and its relevance to conflict management in contemporary church leadership. Employing a qualitative method with a narrative analysis approach to Numbers 16, the study finds that Korah's rebellion was not merely a struggle for authority but also a rhetorical contest that employed narratives of equality and accusations of abuse of power to shape the community's perceptions. In response, Moses demonstrated a leadership pattern characterized by self-regulation and the use of fair procedures, the willingness to clarify accusations against his integrity, and prioritizing the well-being of the community amid a crisis of trust. These findings suggest that leadership legitimacy is grounded not in domination or popularity, but in faithful responsibility for the welfare of the community.